Best practices for teaching psychosomatic obstetrics and gynecology. (13th January 2023) - Schaffir, Jonathan; Pramataroff-Hamburger, Vivian
Abstract: Psychosomatic obstetrics and gynecology (POG) encompasses a wide variety of topics. While specialists in this field agree that it is important for practicing clinicians to be familiar with psychosomatic issues related to women's health, there is no consensus about the best practices for teaching and assessing this knowledge, or even which are the topics that should be included. By examining existing literature on educational methodology, this paper aims to suggest best practices that are proven useful in teaching issues related to POG. The paper considers learning objectives for what should be taught, recommendations as to best practices for curriculum delivery, and suggestions for how to assess learners' ability to meet the objectives. Establishing guidelines for teaching POG may be useful for learners at different levels and in various settings.